IMPROVING STUDENTS’ READING COMPREHENSION THROUGH INFORMATION GAP TECHNIQUE IN TEACHING NARRATIVE TEXT - Vonny Purbowati; Rahayu Apriliaswati; Luwandi Suhartono (Universitas Islam Ogan Komering Ilir Kayuagung, 2022)
This research aimed to investigate how the information gap technique improved students reading comprehension on narrative text to the 8th-grade students. This research was conducted by using classroom action eesearch. The subject of this research was the 8thgrade students in class VIII C. In collecting data, the writer used an observation checklist table, field note and reading test. The result showed that the students’ abilities to comprehend narrative text improved through information gap technique. It was shown by students enthusiasm to pay attention, and followed every activity during teaching and learning process used information gap technique as teaching a technique. It can be concluded that information gap technique can be used as a technique to improve student's reading comprehension on narrative text